Students' Perceptions about Evaluation of Speaking Skills (Mahârah Kalâm) Through Youtube Channel - Rahmat Satria Dinata; Musalwa Musalwa; Meliza Budiarti (Lisaanuna Ta`lim Al-Lughah Al-Arabiyah: Jurnal Pendidikan Bahasa Arab, 2021)
The purpose of this study was to analyze students' perceptions of the Arabic speaking skills evaluation using YouTube as an evaluation medium. This study used descriptive research which aims to describe the results of the analysis related to students' perceptions of the Arabic speaking skills evaluation using YouTube as an evaluation medium. Because of the large amount of data and information obtained from students, the researchers used data collection methods through questionnaires. Findings show that first, the students agree to use YouTube as a medium for evaluating speaking skill (maharah kalam). Second, the students were happy with the use of YouTube as a medium. evaluation of speaking skill (maharah kalam) and students felt that their motivation was increased by using YouTube as a medium. Third, students feel they practice using Arabic by using YouTube as a medium for evaluating speaking skill (maharah kalam) then it can be concluded that the evaluation construction is valid because when evaluating speaking skill (maharah kalam), students must speak, or the aspect of speaking that is measured. Fourth, The students' perceptions of the objectivity of lecturers in assessing the videos were good. Fifth, that students agree to use YouTube as an evaluation medium in other courses